Costs of means of payment for consumers: Literature review and some sensitivity analyses - Malte Krüger; Franz Seitz (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2025)
Payment costs for consumers are difficult to determine, are not recorded in an internationally harmonized manner and vary significantly from country to country. They are incurred in many forms, for example as fees for account management, for cash withdrawals at ATMs or for payment cards; but also as financial damage in the event of loss or fraud. On the other hand, this also includes time costs, e.g. for cash withdrawals or the payment process, and costs of data disclosure. To determine the total costs and for international comparisons, different key figures are calculated, such as the cost per transaction, as a percentage of the transaction value or relative to GDP. After clarifying the concept of costs, the focus of our paper is on a critical review of the literature on cost studies at the consumer level. In particular, the results of existing work are compared, the most important cost categories are identified and sensitivity analyses are carried out. We find some key cost drivers and show how the results are driven by key assumptions.
Keywords: D12; E41; E42; 330; cash; debit card; credit card; costs; consumer